PELANGGARAN HAK AHLI WARIS ANALISIS KASUS PENGUASAAN DAN PENGALIHAN HARTA PENINGGALAN - idah, yusna zaidah; Putri Purnamayanti; Fauziah Hayati; Erma Sauva Asvia (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
ABSTRACT The inheritance of property by the biological mother of the heirs is not appropriate, making it interesting to conduct research to understand the background and impact on the social lives of these heirs. Thru empirical legal research and a qualitative approach, using the heirs and community leaders as research subjects, it was found that the method of controlling the inheritance by one of the heirs was by selling the inheritance without prior consultation with the other heirs and then distributing it in portions that did not comply with the applicable regulations. In fact, the land still has the status of joint property between the heir and his former wife. This action is motivated by the relevant party's (the inheriting parents') desire to protect their child's (the heir's) property rights from being misused by other heirs. This then led to family conflict between the heir's wife and the heir's mother. The action of one of the heirs is not appropriate, because before selling and distributing the property, there should have been consultation with the other heirs (the deceased's former wife and children). Because the land is still an inheritance, which includes joint property between the heir and his wife. The former wife is entitled to the first share of the jointly owned property included in the inheritance, in addition to the inheritance taken from the deceased's share of the jointly owned property. Keywords: Community Property, Estate, Inheritance,